2017
DOI: 10.1111/avj.12590
|View full text |Cite
|
Sign up to set email alerts
|

Students’ opinions on welfare and ethics issues for companion animals in Australian and New Zealand veterinary schools

Abstract: Australasian veterinary students placed more importance on competency in AWE issues associated with clinical practice (such as neutering and euthanasia) than on professional behaviours (such as over-servicing and animal breeding). However, we consider that emphasis should still be placed on developing graduate competency in the latter categories to reflect growing societal concerns about companion animal over-supply and inappropriate professional conduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…For example, they were discussed as part of the veterinary curriculum by Dolby (66), who emphasised that as veterinarians are a key point of contact for the public's understanding of animal welfare, hidden curriculums within veterinary teaching have a longlasting impact. The formation of these hidden curriculums within veterinary teaching have been discussed as a reason for a lack of veterinary empathy by Degeling et al (67), and it is recognised that much of this occurs in the workplace as well as within the classroom (68). Hidden curriculums were referenced in a veterinary animal welfare teaching context, though not explicitly discussed by Whittaker (16), Batchelor et al (69), and Dolby and Litster (70).…”
Section: Hidden Curriculummentioning
confidence: 99%
“…For example, they were discussed as part of the veterinary curriculum by Dolby (66), who emphasised that as veterinarians are a key point of contact for the public's understanding of animal welfare, hidden curriculums within veterinary teaching have a longlasting impact. The formation of these hidden curriculums within veterinary teaching have been discussed as a reason for a lack of veterinary empathy by Degeling et al (67), and it is recognised that much of this occurs in the workplace as well as within the classroom (68). Hidden curriculums were referenced in a veterinary animal welfare teaching context, though not explicitly discussed by Whittaker (16), Batchelor et al (69), and Dolby and Litster (70).…”
Section: Hidden Curriculummentioning
confidence: 99%
“…The rating of these topics by educators was very similar to those by undergraduate veterinary science students who completed the same questionnaire (24)(25)(26)32). The educators' focus on practical issues and avoidance of esoteric issues clashes with a perceived need for veterinarians to embrace animal ethics more actively.…”
Section: Discussionmentioning
confidence: 69%
“…These ratings reflect the everyday need for veterinarians to be conversant in these topics in order to give good advice to clients. Over servicing, cosmetic surgery and shelter medicine were rated as least important as Day One competences, as also found in a parallel student survey (25). This may suggest that students mirror the views of the educators teaching them, but any attempt to ascribe causality will require further investigation.…”
Section: Companion Animalsmentioning
confidence: 66%
“…In the context of this data, it can be said that the higher grade students better understood the rights and responsibilities of the profession of being a veterinarian, as a result of the vocational training that they receive. Degeling et al (2017) reported that Australasian veterinary students placed more importance on competency in AWE issues associated with clinical practice (such as neutering and euthanasia) than on professional behaviors (such as over-servicing and animal breeding).…”
Section: Discussionmentioning
confidence: 99%